2014
DOI: 10.1080/00071668.2013.873772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyme essential oil and selenium on intestine integrity and antioxidant status of broilers

Abstract: 1. This study evaluated the duodenal wall integrity, antioxidant status as well as some immunological parameters of broiler chickens supplemented with 0.5 g Thymus vulgaris essential oil (EO)/kg diet and 0.4 mg Se/kg DM (dry matter) derived from sodium selenite. 2. A total of 192 one-d-old randomly divided chickens of both sexes (Ross 308 hybrid broilers) were divided into 4 treatment groups of 48 birds each. 3. The first group was fed on a nutritionally balanced basal diet (BD). The other three groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 40 publications
6
67
1
Order By: Relevance
“…We also observed a high and unexpected variation between individual samples. This observation is in opposition with the current literature where the use of selenium is usually associated with increased levels of immunoglobulins and GPX, factors associated with healthy chickens (Chen et al, 2014; Placha et al, 2014; Boostani et al, 2015). Under our experimental settings, the exact mechanisms driving these unexpected results remained unidentified.…”
Section: Discussioncontrasting
confidence: 97%
“…We also observed a high and unexpected variation between individual samples. This observation is in opposition with the current literature where the use of selenium is usually associated with increased levels of immunoglobulins and GPX, factors associated with healthy chickens (Chen et al, 2014; Placha et al, 2014; Boostani et al, 2015). Under our experimental settings, the exact mechanisms driving these unexpected results remained unidentified.…”
Section: Discussioncontrasting
confidence: 97%
“…Beside benefits on meat quality, EOs or plant extracts are also reported to improve redox balance in different organs [55,86], and attenuate oxidative injury induced by different physiological stressors [87-89]. Table 5 shows the results of an experiment where different concentrations of ginger root powder and its EOs were fed to broilers raised under heat stress conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study are in agreement with this report. Placha et al (2014) observed that inorganic Se (0.4 mg/kg) significantly increased glutathione peroxidase activity in blood and liver. Also, Wang (2009) concluded that supplementation of nano-Se and sodium Table 5 Effect of organic, inorganic and nano-selenium on relative weights (% of body weight) of liver and lymphoid organs at days 21 and 42 of age.…”
Section: Discussionmentioning
confidence: 89%